Ultra-Sensitive Quantum Sensor for Detection of Pollutants in Water - Mohammad Fathoni; Amin Zaki; Faisal Razak (Yayasan Adra Karima Hubbi, 2024)
Water pollution by hazardous substances, such as heavy metals and industrial chemicals, is a global problem that threatens the sustainability of ecosystems and human health. Early detection of these pollutants is essential to prevent further damage. This study aims to evaluate the effectiveness of ultra-sensitive quantum sensors in detecting pollutants in water at very low concentrations. The method used in this study is laboratory and field experiments, by comparing the performance of quantum sensors and conventional sensors in detecting heavy metals and other chemicals in water. The results show that quantum sensors have a much higher sensitivity compared to conventional sensors, with the ability to detect contaminants up to lower concentrations. Quantum sensors can detect lead (Pb) at 0.1 ppb, while conventional sensors can only detect at 0.4 ppb. In conclusion, quantum sensor technology can provide a more efficient and sensitive solution for water quality monitoring, and it has great potential to be implemented in a wider range of environmental monitoring systems. Further research is needed to overcome cost constraints and improve the integration of these technologies in water monitoring in the field.